ANALYZING NETWORKS: A STUDY OF SOCIAL MEDIA NETWORK ANALYSIS - Beatriz, Priskilla; Salim, Clement Lintanglor; Hartono, Stefhanie Angelina; Michael, Maxilianus; Surya, Nathanael (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This paper aims to increase students' understanding of Tarakanita 2 Pluit High School regarding the benefits, network analysis and long-term impact of social media connections. The problems identified involve students' lack of understanding of the positive and negative benefits of social media network analysis. Community education methods were chosen as the main approach to achieve this goal. This method involves a seminar activity entitled